1993
DOI: 10.1007/bf00839964
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of adult-onset motor neuron disease: a prospective study based on the Scottish Motor Neuron Disease Register

Abstract: The Scottish Motor Neuron Disease Register (SMNDR) is a prospective, collaborative, population-based project which has been collecting data on incident patients since 1989. In this report we present the clinical features of 229 patients with motor neuron disease (218 sporadic and 11 familial) diagnosed in 1989 and 1990 and compare their prognosis with previous studies of survival. The overall 50% survival from symptom onset was 2.5 years (95% CI, 2.2-3.0) and 5-year survival 28% (95% CI, 20-36%). The presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
75
4
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 34 publications
5
75
4
1
Order By: Relevance
“…The average age at diagnosis fell within the norms of population-based studies of 57 to 68. 1,4,5,7,9,15,16 Although several authors report increased survival in referral cohorts compared to population-based cohorts, 1,13 the median survival of 15.8 months in our registry is similar to that reported for other series. 9 The concern for bias generated by the exclusion of long-term survivors was partially addressed by re-analysis of the cohort after exclusion of those patients surviving .7 years after onset.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The average age at diagnosis fell within the norms of population-based studies of 57 to 68. 1,4,5,7,9,15,16 Although several authors report increased survival in referral cohorts compared to population-based cohorts, 1,13 the median survival of 15.8 months in our registry is similar to that reported for other series. 9 The concern for bias generated by the exclusion of long-term survivors was partially addressed by re-analysis of the cohort after exclusion of those patients surviving .7 years after onset.…”
Section: Discussionsupporting
confidence: 88%
“…It is unclear which, if any, of the clinical variables are important for predicting survival. Previous studies of ALS populations identified several negative prognostic factors, [1][2][3][4][5][6][7][8][9][10][11][12][13] including older age at onset, female sex, and bulbar onset. As there is so much inconsistency in the published literature regarding the relative importance of prognostic factors, clinicians are challenged to provide a well-reasoned prognosis to newly diagnosed patients.…”
mentioning
confidence: 99%
“…1,2 The incidence of sporadic ALS ranges between 1.5 and 2.7 per 100,000 population/year (average 1.89 per 100,000/year) in Europe and North America. [3][4][5][6][7] In patients with ALS, MR imaging of the brain may show signal-intensity abnormalities, namely a hyperintense signal intensity in PD-T2 [8][9][10] and FLAIR [11][12][13][14] MR images in the CST from the white matter of the precentral gyrus through the corona radiata and posterior limb of the internal capsule down to the brain stem, consistent with CST degeneration.…”
mentioning
confidence: 99%
“…A myotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by rapidly progressive paralysis leading to death from respiratory failure. Population-based epidemiological studies indicate that the median survival of ALS patients is 20-36 mo (1)(2)(3). Demographic and clinical features, as well as riluzole and certain symptomatic therapies, are known to modestly modify survival, but the influence of genetics on the rate of disease progression and survival is not known (4).…”
mentioning
confidence: 99%